SPERM STRUCTURAL AND MOTILITY CHANGES DUE TO AN ANTICANCER DRUG CYCLOPHOSPHAMIDE IN MALE SQUIRREL FUNAMBULUS PENNANTI (WROUGHTON) - M. S. SASTRY; Z. N. KASHMIRI (The Bioscan, 2011)
The effect of an anticancer drug, Cyclophosphamide on the sperm count, motility and morphology has been evaluated. Cyclophosphamide in two different doses i.e. 6mg for 30 days and 12mg for 15 days was administered whereas same amount of normal saline was given to control animals. The low dose treatment resulted into a condition between normospermia and oligospermia whereas the high dose treatment resulted into oligospermia. Treatment also resulted into either immotility, “rotational” or “forward progressive movement”, however, high dose treatment showed hampered motion due to different types of coiling in the tail. The head abnormalities included pyriform, amorphous, compressed, smallness, lateral displacement of head, loss of DNA or vacuolation or stippling in the nucleus, loss of acrosome or its vacuolation or its throwing into bulb-like structure as well extreme enlargement of head indicating diploidy. Low dose treatment mainly resulted into bifurcation or multifurcation of tails but high dose treatment resulted into specialized types of tail coiling.